2020
DOI: 10.1186/s13048-020-00639-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA CTBP1-AS2 sponges miR-216a to upregulate PTEN and suppress endometrial cancer cell invasion and migration

Abstract: Background: Although lncRNA CTBP1-AS2 has been functionally analyzed only in cardiomyocyte hypertrophy and diabetes, analysis of TCGA dataset revealed its downregulation in endometrial carcinoma (EC), indicating its involvement in EC. Results: In this study we found that CTBP1-AS2 was downregulated in EC and correlated with poor survival. MiR-216a might form base pairs with CTBP1-AS2 based on RNA-RNA interaction, which was confirmed by luciferase activity assay. Interestingly, upregulation of PTEN was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Another critical conclusion was that exosomal miR‐139‐5p could downregulate PTEN and trigger the ERK/MMP‐2 pathway. It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas 31–33 . More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical conclusion was that exosomal miR‐139‐5p could downregulate PTEN and trigger the ERK/MMP‐2 pathway. It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas 31–33 . More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas. [31][32][33] More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6. 34 Moreover, strengthened PTEN in HTR-8/SVneo cells displayed partial degeneration of the improved cell infiltration prompted by miR-21.…”
Section: Ameliorative Effect Of Exosomes On Pe Ratsmentioning
confidence: 99%
“…Although a tumor-suppressive role for miR-216a has been reported ( Zhang et al, 2017 ), this miRNA was identified as an oncogenic miRNA in many cancers, including EC ( Wang Q.A. et al, 2020 ), ovarian cancer ( Liu et al, 2017 ), hepatocellular carcinoma ( Xia et al, 2013 ), and renal cell carcinoma ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2020 ), ovarian cancer ( Liu et al, 2017 ), hepatocellular carcinoma ( Xia et al, 2013 ), and renal cell carcinoma ( Chen et al, 2018 ). The direct target genes of miR-216a include PTEN in EC ( Wang Q.A. et al, 2020 ), and PTEN and SMAD7 in hepatocellular carcinoma ( Xia et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Editors-in-Chief has retracted this article [ 1 ] due to lack of evidence that the study has received ethics approval. After publication it has come to the Editor’s attention that in the body of the article the authors state that their study was approved by the Ethics Committee at the First Hospital of Lanzhou University.…”
mentioning
confidence: 99%